Fear of hypoglycaemia in adults with Type 1 diabetes: results from Diabetes MILES – The Netherlands. Issue 10 (28th March 2015) - Nefs, G.; Bevelander, S.; Hendrieckx, C.; Bot, M.; Ruige, J.; Speight, J.; Pouwer, F.
Abstract Aims To examine sociodemographic, clinical and psychological factors associated with fear of hypoglycaemia in adults with Type 1 diabetes. Methods Data were obtained from Diabetes MILES – The Netherlands, an online self‐report national survey. This cross‐sectional analysis focused on participants with Type 1 diabetes who completed the 18‐item Hypoglycaemia Fear Survey – Second Version Worry subscale (HFS–II–W; possible total score range 0–72, higher scores indicating higher fear) (n = 288). To explore correlates of fear of hypoglycaemia, a hierarchical linear regression analysis was performed in participants with full data on sociodemographic, clinical and psychological factors (n = 232; younger and more highly educated than those excluded). Results HFS–II–W mean score was 11.1 ± 11.1. Gender, age, education and having a partner (model 1) were not associated with fear of hypoglycaemia. In model 2, history of severe hypoglycaemia (irrespective of number of events) was associated with (greater) fear of hypoglycaemia, whereas diabetes duration, pump therapy and HbA1c were not. Type D personality was positively correlated (model 3), as were symptoms of depression, but not anxiety (model 4). Adding loneliness (model 5) did not improve the model. The fully adjusted analysis showed that fear of hypoglycaemia was associated with depressive symptoms (β = 0.38, P < 0.001) and history of hypoglycaemia (1–2 events: β = 0.30, P < 0.001; ≥ 3 events: β = 0.19, P = 0.002). Total explained variance was 23%. Conclusions Depressive symptoms and history of hypoglycaemia are associated with fear of hypoglycaemia in adults with Type 1 diabetes. These factors may help to identify people with excessive fear, who may particularly benefit from interventions to reduce hypoglycaemia risk and worries.